Asia Pasifik: Analisis faktor ekonomi dan sosial yang mempengaruhi indeks pembangunan manusia 2018-2023 - Laksono, Budi; Pratomo, Dimas; Selvina, Mia (Nur Science Institute, 2025)
This study aims to analyze the factors that influence the Human Development Index (HDI) in the Asia Pacific, that is, the level of health measured by life expectancy at birth, education measured by average years of schooling, and a decent living rate reflected by gross national income per capita. This research uses a quantitative approach and uses panel data regression analysis for the period 2018-2023. Based on the statistical results that researchers have carried out, the economic growth variable has a positive and insignificant effect on the human development index (HDI), the health level variable has a significant positive effect on the human development index (HDI), the education level variable has a positive and significant effect on the human development index (HDI). The variable of living conditions has a positive and significant effect on the human development index (HDI). Simultaneously, the variables of economic growth, health level, education level, and livable rate have a positive and significant effect on the human development index (HDI).